Evaluation of Aflatoxins and Pesticide Residues in Fresh and Different Processed Mushrooms (Bangladesh Journal of Scientific and Industrial Research, 2009)
Mushrooms are becoming popular to us due to their nutritional, medicinal and therapeutic values. Toxicity of aflatoxins, presence of DDT and heptachlor as pesticide residue are rare in edible mushrooms but not non-existent. So an attempt has been made to determine its presence and to the same quantify using HPLC and GC. Total seven categories of mushrooms and mushroom-based food products were analyzed. Among them (6 samples) 85.72% of the total was found to be free from aflatoxins. On the other hand, 5.53282 μgkg-1 of aflatoxin B1 was found to be present in canned Button mushrooms (Agaricus spp).The results revealed that 14.28% (1 sample) of samples were toxicated by aflatoxin B1, compare to the total samples analyzed including the imported was in the form of processed/preserved mushrooms. In the present experiments it was also observed that there were no aflatoxins in fresh-cut mushrooms and in the recently developed Mushroom-juice even in dried and powdered as processed Oyster mushrooms (Pleurotus ostreatus) which are being widely cultivated in Bangladesh. No pesticide residue such as DDT or heptachlor was detected in any of the samples examined. Key words: Mushrooms, Oyster, Button, Aflatoxins, DDT, Heptachlor; Pesticide residue.  DOI: 10.3329/bjsir.v44i2.3671 Bangladesh J. Sci. Ind. Res. 44(2), 193-198, 2009